Treason and masculinity in Medieval England : gender, law and political culture / E. Amanda McVitty. - McVitty, E. Amanda (Gender in middle ages ;, 2020)
Groundbreaking new approach to the idea of treason in medieval England, showing the profound effect played by gender.